Liberalization of European migration and the immigration of skilled people to Sweden - Olof Ejermo; Yannu Zheng (IZA Journal of Development and Migration, 2018)
Migration policies can have a strong impact on the selection of immigrants, who in turn can affect the host country's innovation development. This paper examines the effects of the liberalization of migration on the skill composition of immigrants from the EU-15 to Sweden after the inception of the European Economic Area (EEA) in 1994. We examine its effect on immigrants' education levels and probability of becoming an inventor, comparing immigrants from the EU-15 with those from other developed regions in difference-in-differences regressions. The results show that the liberalization of migration had a negative effect on the educational profile of new EU-15 immigrants in the short run, but there is no such effect in the long run. Moreover, the liberalization of migration has no systematic effect on the EU-15 immigrants' probability of becoming an inventor in neither the short nor the long run. These patterns are consistent with the theoretical implication that reduction in migration costs associated with the EEA mainly stimulated migration from the lower end of the education distribution.
Keywords: J15; J24; N30; O31; 330; Human capital; Immigration; Innovation; Selection; Skill level